When the Counterpart Chooses the Opposite: The First Mover’s Anticipation and Evaluation of the Final Feedback in Gambles - Zheng, Jiehui; Wang, Lei; Meng, Liang (Frontiers in Neuroscience, 2022)
This research examines the effect of response consistency on the first mover’s anticipation and evaluation of the performance feedback. In a two-player gambling task, the participant played as the first mover while the confederate served as the second mover, who made their gambles in sequence. A more pronounced feedback-related negativity (FRN) was observed when the first mover noticed that the second mover chose a different option from him/her. An enlarged stimulus-preceding negativity was observed when the first mover was anticipating the final feedback. Interestingly, consistent responses gave rise to a more pronounced FRN difference wave (d-FRN) during the feedback stage. Taken together, these results suggest that response discrepancy would modulate the first mover’s anticipation and evaluation of the final feedback in gambles.